Impact of obesity on factor VIII and von Willebrand factor levels in patients with Type 1 von Willebrand disease and low von Willebrand factor: An analysis of the ATHNdataset. Issue 1 (7th December 2021) - Schaefer, Beverly A.; Cheng, Dunlei; Kouides, Peter
Abstract: Introduction: Obesity is associated with endothelial dysfunction, haemostatic and fibrinolytic disturbances, however the impact of obesity on von Willebrand factor (VWF) is unclear. Aim: The aim of this study was to test our hypothesis that the prevalence of obesity is higher among participants with low VWF (LVWF) compared to type 1 von Willebrand disease (T1VWD). Methods: A retrospective review of the ATHNdataset as of March 2018 was performed. Participants were categorized as T1VWD if their VWF ristocetin cofactor activity was 30 IU/dL and LVWF if the values were 30–50 IU/dL, and by the NIH definitions for body mass index (BMI) for adult participants (≥ 18 years of age) or BMI z‐score for paediatric participants (< 18 years). Results: The prevalence of obesity was not significantly different between adults with T1VWD ( n =  186) and LVWF ( n  = 362) (32% vs 36%; p =  .345). The mean factor VIII (FVIII) increased with increasing BMIs in both groups. In the paediatric cohort (T1VWD, n  = 583; LVWF, n  = 1702), there was no difference in the prevalence of obesity, but BMI was positively correlated with mean FVIII ( p  < .001). Children < 10 years were 27.6% more likely to be diagnosed with T1VWD compared to > 10 years. Conclusion: Among participants in the ATHNdataset, the prevalence of obesity was similar among those with LVWF and T1VWD. However, higher BMI levels were associated with elevated FVIII. Further research is needed to evaluate the impact of obesity on bleeding phenotype and treatment practices.